Yorùbá Ethics of Interpersonal Relations in Ọbasá’s Poetry - Ayodele Solomon Oyewale (Yoruba Studies Review)
In the context of Yorùba interrelation, every human being is involved with ́ a clearly defined tradition laced with mutual benefits. The custom of human interpersonal relationship and the challenges thereof are critical issues in modern Yorùbá society. The themes of Yorùbá ethics as related to interpersonal relation are prominent in Obasa ̣’s poetry. In this essay, we identify and ́ analyze the ethical themes in Obasa ̣’s poetry and compare the poet’s engagement with the Yorùbá philosophy with a view to establish their relevance to the contemporary Yorùbá society.